Nano-enabled biosensors in early detection of plant diseases - Chaturvedi, Ambika; Tripathi, Deepti; Ranjan, Rajiv (Frontiers in Nanotechnology, 2025)
Plant disease outbreaks are raising concerns about global food security. Pathogenic evolution and continuous climate changes increase the threat to agriculture and necessitate disease surveillance. To prevent future outbreaks and maintain agricultural sustainability advanced tools are required. Nowadays various types of nanobiosensors such as electrochemical, piezoelectric, thermal, optical, and Fluorescence resonance energy transfer (FRET)-based biosensors are used to predict disease-associated pathogens, toxins, and abiotic stress. Nanobiosensors, provide quick detection of diseases and may protect from future pandemics as they overcome the time dependency of traditional methods and provide real-time monitoring. The incorporation of various nanoparticles with biosensors such as chitosan nanoparticles, silver nanoparticles (AgNPs), gold nanoparticles (AuNPs), multiwalled carbon nanotubes (MWCNTs), and graphene oxide, etc., facilitates the precise detection of various toxins, pesticides, and disease-causing pathogens in plants. Furthermore, the integration of portable devices and artificial intelligence (AI) increases their practical application in agricultural monitoring. Despite their promising aspect, issues with sensor stability, large-scale development, and cost-effectiveness also need to be addressed. Future studies are more concerned with improving durability, multiplex detection ability, and user-friendly field application. To enhance agricultural output, it is necessary to develop an early disease diagnosis approach that is heavily dependent on the ongoing development of cost-effective nanobiosensors. This review focuses on the recent studies of various nanobiosensors development and their operation mechanism for pathogen detection. Additionally, challenges associated with the worldwide acceptance of nano biosensors are also addressed. Overall, nanobiosensors are new-edge technology that enhances plant disease management strategies and risk mitigation in food security.